Real-time interactive heart illustration platform via hardware accelerated rendering - Lei Zhang; Changqing Gai; Kuanquan Wang; Wangmeng Zuo (2011 3rd International Conference on Advanced Computer Control, 2011)
Real-time interactive visualization plays an important role in the analysis of 3D cardiac imaging data and the assessment of electrophysiological simulation result. Recently, the graphics programmable processor unit (GPU), an increasingly convincing acceleration approach, has been widely adopted in various graphics, visualization, and scientific computing applications. In this paper, we present a GPU-based volume visualization approach for real-time interactive human heart illustration. In our scheme, we first design the transfer function by constructing a lookup table, and adopt a slice-based direct volume rendering method for real-time visualization. Then, a real time heart tissue isolation strategy is used to illustrate each tissue individually. Finally, we design several interactive tools and implement a platform for the effective visualization of cardiac tissues.